Pengukuran Tingkat Kematangan Manajemen Risiko Sistem X pada PT. Y Menggunakan Framework Risk IT Domain Risk Governance - Triyani Sylvia Ferrore; Diana Trivena Yulianti (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2016)
Information technology has long been used in business processes at the PT.Y and are expected to provide added value to the achievement of enterprise goals. In addition to its benefits, the application of information technology also contains risks that may affect the business process itself, causing losses for the enterprise. Therefore, enterprise must understand and anticipate any potential risks that may occur. Application of good information technology risk management aim to reduce the negative impacts of risk that may arise. To find out the extent to which enterprise manage the risks associated with information technology it needs to be evaluated. The research will use the Risk IT framework with Risk Governance domain approach as an information technology risk management standards issued by ISACA to evaluate the implementation of risk management governance at the PT. Y. The evaluation process will be based on a maturity model that has been defined by the Risk IT framework to measure the maturity level of information technology risk management governance conditions at the PT. Y.